2014
DOI: 10.1158/1078-0432.ccr-14-0459
|View full text |Cite
|
Sign up to set email alerts
|

Lung Squamous Cell Carcinomas with Basaloid Histology Represent a Specific Molecular Entity

Abstract: Purpose: The basaloid carcinoma (pure) and the (mixed) basaloid variant of lung squamous cell carcinoma (SCC) have a dismal prognosis but their underlying specific molecular characteristics remain obscure and no therapy has proven to be efficient.Experimental Design: To assess their molecular specificity among other lung SCCs we analyzed DNA copy number aberrations and mRNA expression pangenomic profiles of 93 SCCs, including 42 basaloid samples (24 pure, 18 mixed).Results: Supervised analyses reveal that pure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 28 publications
6
35
1
Order By: Relevance
“…Proteoglycans have an indispensable role in the tumor microenvironment, and as a result, many studies have described their potential use as target genes, biomarkers, and active agents . Moreover, it has been found that mutations in cell cycle genes can affect the differentiation of squamous cells in the course of modern anticancer treatment research . Pathways in cancer, which describes important signaling pathways such as Wnt signaling and T‐cell receptor signaling, is also an important factor in the progression of NSCLC and development of squamous cell carcinoma of the lung …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteoglycans have an indispensable role in the tumor microenvironment, and as a result, many studies have described their potential use as target genes, biomarkers, and active agents . Moreover, it has been found that mutations in cell cycle genes can affect the differentiation of squamous cells in the course of modern anticancer treatment research . Pathways in cancer, which describes important signaling pathways such as Wnt signaling and T‐cell receptor signaling, is also an important factor in the progression of NSCLC and development of squamous cell carcinoma of the lung …”
Section: Discussionmentioning
confidence: 99%
“…51,52 Moreover, it has been found that mutations in cell cycle genes can affect the differentiation of squamous cells in the course of modern anticancer treatment research. 53,54 Pathways in cancer, which describes important signaling pathways such as Wnt signaling and T-cell receptor signaling, is also an important factor in the progression of NSCLC and development of squamous cell carcinoma of the lung. 55,56 To further validate and screen the target genes, we performed a topological analysis in the PPI network.…”
mentioning
confidence: 99%
“…This finding was consistent with previous studies. 9,11 As more than half of lung SqCC patients may be candidates for molecularly targeted treatment, 13 the correlation between the histological subtypes and geneexpression data should be further investigated in the future. This finding might suggest therapeutic effect on the survival of patients with lung cancer and CPFE.…”
Section: Discussionmentioning
confidence: 99%
“…34 In the thymus, cancers with basaloid features show a more varied histology (including a wide range of proliferative activities, common macropapillary growth pattern and association with cysts) and a broader spectrum of clinical aggressiveness. 35 Genetic data are sparse and not overlapping with those of pulmonary basaloid squamous cell carcinoma.…”
Section: Novelties In the New Who Classification Of Mediastinal Tumorsmentioning
confidence: 99%